A taxonomic revision of Cardamine L. (Brassicaceae) in New Zealand - Heenan, Peter B. (Phytotaxa, 2017)
A taxonomic revision of the cosmopolitan genus Cardamine is presented for New Zealand. Previous systematic research and the taxonomic history of Cardamine in New Zealand is reviewed, and a phylogenetic analysis of DNA sequences shows most of the species of Cardamine in New Zealand and Australia are closely related. Forty one taxa indigenous to New Zealand are recognised, with thirty-one species newly named and described, ten previously named taxa are accepted, including C. depressa with two subspecies and a new name is provided for one species. An additional four species are accepted as naturalised in New Zealand. Descriptions are presented for all taxa, along with information on distribution, habitats and conservation status. All taxa are illustrated, distribution maps provided, and a dichotomous key presented to assist with identification.